Adjusting the Valence State of Vanadium in VO2(B) by Extracting Oxygen Anions for High‐Performance Aqueous Zinc‐Ion Batteries. Issue 3 (28th December 2020) - Zhang, Wenwei; Xiao, Yao; Zuo, Chunli; Tang, Wen; Liu, Gangyuan; Wang, Shiyu; Cai, Wanyue; Dong, Shijie; Luo, Ping
Abstract: VO2 generally has a higher theoretical capacity and layered structure suitable for the intercalation/extraction of zinc ions. However, Zn 2+ ions with high charge density interact with the crystal lattice and limit further improvement in electrochemical performance. Defect engineering is a potential modification method with very promising application prospects, but the established procedures for preparing defects are complicated. In this study, VO2– x (B) with oxygen deficiency is prepared by a simple solution reaction with NaBH4 . The presence of oxygen deficiencies is confirmed by positron annihilation lifetime spectroscopy, UV/Vis absorbance spectroscopy and others. Owing to the presence of oxygen defects, the aqueous Zn/VO2– x (B) battery exhibits improved specific capacity, excellent reversibility, and structural stability. Ex situ characterization techniques are employed to demonstrate the reversible insertion‐extraction mechanism of Zn 2+ ions from and into the host material. In addition, the Zn/VO2– x (B) batteries still exhibit considerable electrochemical performance, even with high‐loading electrodes (about 4 mg cm −2 ). Abstract : Vacancy clearly now : Oxygen vacancies were introduced into VO2‐ x by using simple solution reaction. Oxygen defects promote the ability to store zinc ions. This study provides an economic method to prepare such vacancies and enriches characterization (positron annihilation lifetime and UV/Vis spectroscopy) of cathodes in aqueous zinc‐ion batteries.